ADOPTION OF FINTECH SOLUTIONS AND THEIR ROLE IN ENHANCING CORPORATE FINANCIAL GROWTH - Bhilare, Meghana (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In order to better understand how various industries and company sizes are affected by this shift, this research examines the link between the adoption of FinTech solutions and corporate financial growth. The purpose of the study is to ascertain whether or not FinTech adoption has a substantial impact on financial performance and whether or not adoption rates vary noticeably across industries according to sector and size. The studies evaluates the results of various FinTech technologies on commercial enterprise operations and financial outcomes through using quantitative data analysis. Examples of these merchandise consist of digital payment systems, accounting automation software program, and investment management structures. The findings demonstrate a strong positive link between the adoption of FinTech and increased financial growth, suggesting that businesses using these technologies have seen significant increases in productivity, cost savings, and overall performance. The present study additionally reveals that the adoption of FinTech solutions differs throughout industries, with larger organizations and those in IT and finance being much more likely to include these economic technology. The study admits its limitations, notably in sample diversity and dependence on self-reported data, even if the results provide insightful information. Future research may investigate the long-term implications of FinTech on financial expansion and new technologies as they arise, providing enterprises with tactical direction for navigating the dynamic digital ecosystem.